Promise and threat:living with nuclear in the Finnish context - Strauss-Mazzullo, Hannah (Routledge, 2020)
The decision to build a new nuclear power plant on a greenfield site in Pyhäjoki, Northern Finland, is so far unprecedented in Western societies. It comes after Fukushima, after other European countries’ wish to phase out nuclear power and after Finland has started building a final repository for spent nuclear fuel. It also stands in the context of national discussions around the mining of uranium, a possibility not rejected by all as it would mean assuming responsibility for the entire fuel cycle, from beginning to end. Generally, nuclear power production is considered a means of becoming independent of electricity imports (especially from Russia) and, at the same time, not emitting greenhouse gases. The safe and efficient handling of the high-risk technology since the 1970s has become a source of national pride, and thus, catastrophes are considered unlikely – although this belief is frequently challenged when small scandals surface from the ongoing construction of the nation’s fifth nuclear power plant unit further south. In a country of “few resources,” nuclear energy production (and perhaps uranium exploitation in the future) function as tools toward happiness or contentment.